13C and 15N NMR shieldings of 1, 2, 4-diazaphospholes in the solid state and in solution. Issue 1 (2001) - Claramunt Claramunt, R.M. R.M.; López López, C. C.; Schmidpeter Schmidpeter, A. A.; Willhalm Willhalm, A. A.; Elguero Elguero, J. J.; Alkorta Alkorta, I. I.
Abstract : The solid state 13 C and 15 N CPMAS NMR spectra of 3, 5-di- tert -butyl-1, 2, 4-diazaphosphole4 and 3, 5-diphenyl-1, 2, 4-diazaphosphole5 have been recorded. The X-ray structure of the first compound was already known (it is a cyclic dimer with localized N–H protons) while the structure of the second cannot be determined due to the difficulty to grow suitable single crystals. NMR results pointed out that4 is a "classical" compound while5 is probably a tetramer showing Intermolecular Solid-State Proton Transfer (ISSPT). GIAO/ab initio calculations have been carried out to estimate the absolute 1 H, 13 C and 15 N shieldings. The agreement with the experimental chemical shifts is good enough to assign the signals of carbons C-3 and C-5.